Furthering transgender inclusion in the workplace: advancing a new model of allyship intentions and perceptions. Issue 9 (15th May 2023) - Fletcher, Luke; Marvell, Rosa
Abstract: There remains a significant knowledge gap in HRM regarding the inclusion of transgender (henceforth 'trans') workers. We examine and apply the emerging concept of allyship (a specific form of active support and advocacy for minority groups) to trans workers, and in doing so we advance a new model of allyship intentions and perceptions. We test our model across two studies. The first extends theorising on perceived diversity and inclusion climate (PDIC) and social dominance orientation (SDO) to explain how non-trans workers can exhibit trans allyship intentions. When non-trans workers were presented with a scenario of a co-worker disclosing their trans identity, we find that SDO is negatively related with allyship intentions, yet PDIC moderates this relationship, such that the negative impact of SDO is buffered by the positive influence of PDIC. The second study builds upon theorising on psychological safety and authenticity to explain how perceived allyship facilitates the wellbeing of trans workers. We find, in a survey of trans workers, that perceived allyship is positively associated with psychological safety and authenticity at work; and is indirectly related to work engagement via the former and to life satisfaction via the latter. We provide critical insights into how allyship can be advanced to understand and support trans inclusion.